1992
DOI: 10.1152/ajpcell.1992.263.4.c810
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy reduces alpha 1 and not beta 1 Na(+)-K(+)-ATPase mRNA expression in rat distal nephron

Abstract: The abundance of mRNA of alpha 1-, alpha 2-, alpha 3-, beta 1-, and beta 2-isoforms of Na(+)-K(+)-ATPase was examined in several renal structures of normal and adrenalectomized (ADX) rats. In situ hybridization with 35S-labeled cRNA probes was performed on kidney sections from adult rats. The number of silver grains per unit surface area was quantified over cells of the glomerulus, proximal convoluted tubules (PCT), early distal tubules (EDT), and cortical collecting ducts (CCD). In normal rat kidney, alpha 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 3 publications
4
21
1
Order By: Relevance
“…In the infant kidney, the transcription rate of Na,K-ATPase is directly increased by G C (6). G C do not regulate Na,K-ATPase mRNA in adults (13,14). In adults, Na,K-ATPase mRNA is regulated by MC, at least in aldosterone-sensitive cells (13).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…In the infant kidney, the transcription rate of Na,K-ATPase is directly increased by G C (6). G C do not regulate Na,K-ATPase mRNA in adults (13,14). In adults, Na,K-ATPase mRNA is regulated by MC, at least in aldosterone-sensitive cells (13).…”
mentioning
confidence: 79%
“…The effect of GC is tissue-specific and occurs only in tissues that are rapiclly maturing (9). GC do not seem to be necessary for Na,K-ATI'ase transcription in the adult renal cortex, because adrenalectomy does not affect the abundance of Na,K-ATPase mRNA in proximal tubules (13,14), nor does GC treatment in controll rats alter renal Na,KATPase mRNA (3). In the adult colon, ~t has been reported that GC but not aldosterone increase Na,K.-ATPase mRNA.…”
Section: Control Betamethasonementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to differentially regulated rates of transcription, there is evidence that the translational efficiency of the β-subunit may be several-fold higher than the α-subunit, which may account for equal accumulation of the two subunit proteins in those cells and tissues where α-mRNA is more abundant than β-mRNA. There are several examples of differential control of α-and β-subunit genes in cell systems (Corthésy-Theulaz et al, 1991;Farman et al, 1992;Geering et al, 1989) and one remarkable example among teleosts. Deane and Woo cloned both the α-and β-subunit in S. sarba gill and examined the response to various hormones (Deane and Woo, 2005).…”
Section: The β 1 Transcriptmentioning
confidence: 99%